Proceedings of the Seventh IEEE International Conference on Computer Vision 1999
DOI: 10.1109/iccv.1999.791202
|View full text |Cite
|
Sign up to set email alerts
|

Real-time object detection for "smart" vehicles

Abstract: This paper presents an e cient shape-based object detection method based on Distance Transforms and describes its use for real-time vision on-board vehicles. The method uses a template hierarchy to capture the variety of object shapes; e cient hierarchies can be generated o ine for given shape distributions using stochastic optimization techniques i.e. simulated annealing. Online, matching involves a simultaneous coarse-to-ne approach o ver the shape hierarchy and over the transformation parameters. Very large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
319
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(322 citation statements)
references
References 16 publications
0
319
0
3
Order By: Relevance
“…In [9], moving pixels are grouped in to blobs and using shape features these blobs are classified in to human or non human objects. Gavrila and philomin compared edge images using chamfer distance for human detection [10]. Mikolajczyk et al [11] parts based human detection method containing detectors for front and side profiles of upper and lower body parts, heads and faces.…”
Section: Previous Workmentioning
confidence: 99%
“…In [9], moving pixels are grouped in to blobs and using shape features these blobs are classified in to human or non human objects. Gavrila and philomin compared edge images using chamfer distance for human detection [10]. Mikolajczyk et al [11] parts based human detection method containing detectors for front and side profiles of upper and lower body parts, heads and faces.…”
Section: Previous Workmentioning
confidence: 99%
“…They use human template to find the marching regions in edge map of the inputting image. [27], [28] are based on this method. [28] proposes a direct template matching approach for global shape-based human detection.…”
Section: Related Workmentioning
confidence: 99%
“…[27], [28] are based on this method. [28] proposes a direct template matching approach for global shape-based human detection. [27] is developed form this method and use the hierarchical template to reduce the detection time and solve the occlusion problem to some extent.…”
Section: Related Workmentioning
confidence: 99%
“…The edge map contains most of the shape information for an object, and at the same time is not very sensitive to color changes. Edge features have been widely applied in Chamfer (edge-based) matching [18] and shape context [25] matching. We have found that small blocks centered on the edge pixels, of a distance transform image are expressive local features.…”
Section: Features For Matchingmentioning
confidence: 99%